2005
DOI: 10.1152/jn.00347.2005
|View full text |Cite
|
Sign up to set email alerts
|

Commissural Excitation and Inhibition by the Superior Colliculus in Tectoreticular Neurons Projecting to Omnipause Neuron and Inhibitory Burst Neuron Regions

Abstract: Previous electrophysiological studies have shown that the commissural connections between the two superior colliculi are mainly inhibitory with fewer excitatory connections. However, the functional roles of the commissural connections are not well understood, so we sought to clarify the physiology of tectal commissural excitation and inhibition of tectoreticular neurons (TRNs) in the "fixation " and "saccade " zones of the superior colliculus (SC). By recording intracellular potentials, we identified TRNs by t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
86
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(93 citation statements)
references
References 104 publications
(136 reference statements)
6
86
1
Order By: Relevance
“…This visual discharge is accompanied by a suppression of activity of saccade-related neurons in the SC on the opposite side of the brain. This push -pull relationship between activity in the left and right SCs is mediated by intercollicular inhibition [33,34], and prevents simultaneous programming of incompatible saccades. On prosaccade trials, this visual response was followed closely by a burst of activity beginning just prior to generation of the saccade into the neuron's response field.…”
Section: Neurophysiology In the Superior Colliculus: Fingerprints Of mentioning
confidence: 99%
“…This visual discharge is accompanied by a suppression of activity of saccade-related neurons in the SC on the opposite side of the brain. This push -pull relationship between activity in the left and right SCs is mediated by intercollicular inhibition [33,34], and prevents simultaneous programming of incompatible saccades. On prosaccade trials, this visual response was followed closely by a burst of activity beginning just prior to generation of the saccade into the neuron's response field.…”
Section: Neurophysiology In the Superior Colliculus: Fingerprints Of mentioning
confidence: 99%
“…The experimental arrangements for electrophysiological studies were the same as those described in detail previously (Takahashi et al 2005a(Takahashi et al , 2007. Briefly, the parietal and occipital cortex over the SC was removed bilaterally by aspiration to allow the introduction of stimulating electrodes into the right SC and a recording electrode into the left SC under direct visual observation.…”
Section: E T H O D Smentioning
confidence: 99%
“…TRNs receive excitatory and inhibitory inputs from many areas, such as the visual association cortex, the frontal eye field, substantia nigra pars reticulata, and the cerebellum. Commissural inputs from the opposite SC are also important sources of input to TRNs (Maeda et al 1979;May 2006;Mize 1992;Moschovakis et al 1988;Olivier et al 1998;Takahashi et al 2005aTakahashi et al , 2007.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The rostrocaudal spatial distribution of activity was obtained by including the 45 cells we recorded on the motor map (18 in the 53°zone, 21 in 13°zone and 6 between the zones) plus the 17 SCFNs described by Choi and Guitton (2006). We included SCFNs because (1) a number of studies have suggested that there is no discontinuity between the very rostral and remaining SC map Keller, 1997, 1999;Anderson et al, 1998;Krauzlis, 2005;Hafed et al, 2009), such that inclusion of SCFNs in the spatiotemporal evolution of activity provides a complete picture of map activity and (2) the very rostral SC and the remaining motor map are anatomically linked (Munoz and Istvan, 1998;Takahashi et al, 2005). However, since SCFNs were essentially silent (Choi and Guitton, 2006) until ϳ50 -80 ms after gaze shift end (Fig.…”
Section: Spatial Pattern Of Population Activity On Motor Map For 53°gmentioning
confidence: 99%